Stigma Layanan Konseling Sekolah pada Remaja Pengguna Aktif Platform Kesehatan Mental Digital - Yulianti Manik Allo; Paska La'lang; Yulianti Yulianti; Dita Priskia Nivo Tangkelayuk; Fitrawanti Suba; Asrianti Asrianti (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2026)
This study examines the paradoxical phenomenon among adolescents who actively consume mental health content on digital platforms such as Instagram and TikTok but are reluctant to utilize freely available school counseling services. The research aims to identify specific forms of stigma that hinder adolescents from utilizing school counseling services and analyze them using Erving Goffman's stigma theory. The research method employs a qualitative approach with a library research design, analyzing various scientific literature published from 2013-2025 through content analysis techniques. The research findings reveal six main forms of stigma: perception of school counselors as school police, labeling as troubled students, sign of personal weakness, doubts about confidentiality, distrust in counselor competence, and traumatic experiences. The paradox occurs because digital platforms provide anonymity that protects adolescents' virtual social identity, while face-to-face counseling services are perceived as threatening their social identity. Research implications indicate the need for transformation of school counseling services that integrate digital strategies, ongoing campaigns to change negative perceptions, and enhancement of counselor competence in understanding adolescent digital culture to reduce stigma and improve adolescent access to professional mental health services.